Web browser as computational enviroment - Ong, Wei Teck. (2013)
The language of technical computing has become more and more popular especially for engineers, scientists and even community in academia. The software that comes with the functionality for processing technical computing does not come free and MATLAB is one of them. Situations whereby these people do not have the necessary equipment to process their defined equations may occur. Thus, their tasks are delayed.